Mobilizing Organizational Performance through Robotic and Artificial Intelligence Awareness in Mediating Role of Supply Chain Agility - Tanasarn Panichayakorn; Kittisak Jermsittiparsert (International Journal of Supply Chain Management, 2019)
Tourism industry is lifeline for Thailand as this sector is contributing a lot in country’s GDP. With an increasing flux of tourists, hotel industry is bringing artificial intelligence and robotic awareness in their employees to ensure better performance from all dimensions. Such performance levels are also linked with supply chain agility up to some extent. This paper has aimed to analyze the impact of artificial intelligence and robotic awareness on environmental, operational and economic performance of hotel sector of Thailand. Moreover, mediating role of supply chain agility has also been checked in relationship between the respective empirical linkages. Data was collected from the managing employees of hotel sector of Thailand through a structured instrument and it was then analyzed through confirmatory factor analysis and structural equation modeling. Results have provided the insight that robotic awareness has significant impact of all three dimensions of performance and supply chain agility significantly mediates these relationships in positive direction. This study is novel due to testing supply chain agility as mediator in robotic awareness and performance linkage and also because of taking operational performance as another dimension of performance which was not tested in prior literature. Implications, limitations and future research indications are also given in this study.